2018
DOI: 10.1051/0004-6361/201732225
|View full text |Cite
|
Sign up to set email alerts
|

Probing the use of spectroscopy to determine the meteoritic analogues of meteors

Abstract: Context. Determining the source regions of meteorites is one of the major goals of current research in planetary science. Whereas asteroid observations are currently unable to pinpoint the source regions of most meteorite classes, observations of meteors with camera networks and the subsequent recovery of the meteorite may help make progress on this question. The main caveat of such an approach, however, is that the recovery rate of meteorite falls is low (<20 %), implying that the meteoritic analogues of at l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Nonetheless, spraying of the molten layer seams to be the most plausible explanation for the appearance of refractory elements in the spectra, as was also the conclusion of Borovička (1993). The rationale proposed here can also be supported by the experimental spectra of Drouard et al (2018), which does not consider the spraying of the molten thickness. From the high-resolution spectra, these latter authors observed an overestimation of Na with respect to Fe and Mg and a weak intensity of refractory Ca.…”
Section: Lost City Bolidesupporting
confidence: 57%
“…Nonetheless, spraying of the molten layer seams to be the most plausible explanation for the appearance of refractory elements in the spectra, as was also the conclusion of Borovička (1993). The rationale proposed here can also be supported by the experimental spectra of Drouard et al (2018), which does not consider the spraying of the molten thickness. From the high-resolution spectra, these latter authors observed an overestimation of Na with respect to Fe and Mg and a weak intensity of refractory Ca.…”
Section: Lost City Bolidesupporting
confidence: 57%
“…We present the first wide survey of spectral and physical properties of mm-to dm-sized meteoroids. While the specific material types (e.g., types of chondrites) cannot be distinguished from the low-resolution emission spectra (Borovička et al 2015;Drouard et al 2018), the combination of spectral, orbital, and atmospheric meteor data allows us to reveal the rough composition, structure, and source of meteoroids.…”
Section: Discussionmentioning
confidence: 99%
“…There have been successful models of meteor radiation providing relevant results of relative abundances of the main elements. These models have been mostly applied to individual bright fireball spectra captured in high resolution (Borovička 1993;Trigo-Rodriguez et al 2003;Ferus et al 2018;Drouard et al 2018). In order to survey larger samples of meteor spectra, a simplified method of spectral classification (Borovička et al 2005) has been introduced, which is also applicable to more effective low-resolution video observations.…”
Section: Introductionmentioning
confidence: 99%
“…Borovička, 2001;Borovička et al, 2005;Koten et al, 2006). Laboratory spectroscopic experiment proves that intensity ratios are not informative of the abundance and cannot be used to determine the meteorite analogue (Drouard et al, 2018). Line ratios can be used, at best, to study the trend of elemental content in meteors which happen to possess similar physical conditions (including similar entry velocities, similar strengths and similar excitation temperatures).…”
Section: Abundances Vs Intensity Ratiosmentioning
confidence: 99%